Resin emulsion for water-based ink
By using emulsion particles and carboxylic acid polymer non-metal salts in aqueous inks, combining nitrogen-containing monomers to form a multi-layered resin emulsion, the problem of insufficient scratch resistance and adhesion of aqueous inks is solved, and the problem of insufficient scratch resistance and adhesion of aqueous inks is achieved. Higher printing performance.
Patent Information
- Application Number
- CN202180008452.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-27
- Filing Date
- 2021-01-16
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-01-16
AI Technical Summary
Existing water-based inks have shortcomings in scratch resistance, substrate adhesion and adhesion resistance, making it difficult to meet high-demand printing applications.
The aqueous ink resin emulsion containing emulsion particles and a non-metal salt of a carboxylic acid polymer is prepared by emulsion polymerization technology, and nitrogen-containing atomic monomers such as piperidine monomers and (meth)acrylate are used to form a multi-layer structure. The emulsion particles are used to improve the scratch resistance and adhesive properties of the ink.
It has achieved a significant improvement in scratch resistance, substrate adhesion and adhesion resistance of water-based inks. It is suitable for a variety of printing technologies such as inkjet, flexographic plate, offset plate, etc., which significantly improves the performance of ink.
Smart Images

Figure GDA0005138845640000041 
Figure GDA0005138845640000421
Abstract
Description
Technical Field
[0001] The present invention relates to a resin emulsion for water-based ink. More specifically, the present invention relates to a resin emulsion for water-based ink and a method for producing the same, and a water-based ink containing the resin emulsion for water-based ink. The water-based ink of the present invention can be suitably used as, for example, a water-based ink for inkjet, an ink for flexographic printing, an ink for offset printing, an ink for digital orifice printing, an ink for gravure printing, an ink for screen printing, and the like. The water-based ink of the present invention can be suitably used as a water-based ink for inkjet in particular. Background Art
[0002] Ink is roughly divided into two types: organic solvent-based ink using an organic solvent as a main component of the solvent, and aqueous ink using water as a main component of the solvent.
[0003] In organic solvent-based ink compositions, the main component of the solvent is an organic solvent, so the water resistance is good. However, the organic solvent-based ink composition has poor safety to the human body and produces an odor based on the organic solvent. Therefore, water-based inks have attracted attention in recent years.
[0004] As an aqueous ink composition for forming a coating film having excellent storage stability, anti-curling property, abrasion resistance, water resistance and weather resistance, the following ink composition is proposed: it is an aqueous ink composition containing a resin emulsion containing emulsion particles as an essential component, and further contains at least one water-insoluble curable compound selected from the group consisting of a water-insoluble curable monomer and a water-insoluble curable oligomer, the glass transition temperature of the polymer constituting the above-mentioned emulsion particles is 0 to 120°C, and the minimum film-forming temperature of the above-mentioned aqueous ink composition is 0 to 30°C (for example, see Patent Document 1).
[0005] The above-mentioned aqueous ink composition can form a coating film with excellent anti-curling properties, abrasion resistance, water resistance and weather resistance. Therefore, it can be used to form desired information such as text, patterns, colors, etc. on substrates made of materials such as paper, resin sheets or resin films, metal plates, wood boards, leather, etc. by inkjet printing, flexographic printing, offset printing, digital stencil printing, gravure printing, screen printing, ink ribbons, etc., and can be appropriately used in industrial inks such as printing inks for imparting aesthetics, abrasion resistance, water resistance, weather resistance, etc. to substrates.
[0006] Recently, in the field of inks, there has been a demand for the development of water-based inks that are excellent not only in scratch resistance but also in adhesion to substrates and blocking resistance.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 6258662 Summary of the invention
[0010] Problems to be solved by the invention
[0011] The present invention has been made in view of the above-mentioned prior art, and aims to provide an aqueous ink having excellent scratch resistance, adhesion to a substrate, and blocking resistance; and an aqueous ink resin emulsion that can be suitably used for the aqueous ink and a method for producing the same.
[0012] Means for solving problems
[0013] The present invention relates to the following scheme:
[0014] (1) A resin emulsion for water-based ink, which is a resin emulsion used in water-based ink, characterized in that the resin emulsion contains emulsion particles and a carboxylic acid polymer non-metal salt, the emulsion particles contain a polymer, and the polymer contains a monomer component containing a nitrogen atom-containing monomer;
[0015] (2) A method for producing a resin emulsion for water-based ink, which is a method for producing a resin emulsion used in water-based ink, wherein a monomer component containing a nitrogen atom-containing monomer is subjected to emulsion polymerization to prepare a resin emulsion containing emulsion particles, and the resin emulsion is mixed with a carboxylic acid polymer non-metal salt;
[0016] (3) The resin emulsion for aqueous ink according to (1) above, wherein the nitrogen atom-containing monomer is a piperidine monomer or a nitrogen atom-containing (meth)acrylate;
[0017] (4) The resin emulsion for aqueous ink according to (3) above, wherein the piperidine monomer is piperidine containing a (meth)acryloyloxy group or piperidine containing a (meth)acryloylamino group;
[0018] (5) A method for producing a resin emulsion for water-based ink, which is a method for producing a resin emulsion used in water-based ink, wherein a monomer component containing a nitrogen atom-containing monomer is emulsion-polymerized to prepare a resin emulsion containing emulsion particles, and the resin emulsion is mixed with a carboxylic acid polymer non-metal salt; and
[0019] (6) A water-based ink comprising the resin emulsion for water-based ink described in (1) above and a colorant.
[0020] Effects of the Invention
[0021] According to the present invention, there are provided: an aqueous ink having excellent scratch resistance, adhesion to a substrate, and blocking resistance; and an aqueous ink resin emulsion that can be suitably used for the aqueous ink and a method for producing the same. DETAILED DESCRIPTION
[0022] The resin emulsion for aqueous ink of the present invention contains emulsion particles and a carboxylic acid polymer non-metal salt. The emulsion particles contain a polymer, and the polymer includes a monomer component containing a nitrogen atom-containing monomer.
[0023] The water-based ink of the present invention uses the above-mentioned resin emulsion for water-based ink. Therefore, the water-based ink of the present invention is excellent in scratch resistance, adhesion to substrates, and blocking resistance.
[0024] The resin emulsion for aqueous ink of the present invention can be easily prepared by emulsion-polymerizing a monomer component containing a nitrogen atom-containing monomer to prepare a resin emulsion containing emulsion particles, and mixing the resin emulsion with a carboxylic acid polymer nonmetal salt.
[0025] In the resin emulsion for water-based ink of the present invention, a monomer component containing a nitrogen-atom-containing monomer is used as a raw material for the polymer contained in the emulsion particles. Therefore, by using the resin emulsion for water-based ink, a water-based ink having excellent scratch resistance, adhesion to a substrate, and blocking resistance can be obtained.
[0026] As the nitrogen-containing monomer, for example, piperidine monomer, nitrogen-containing (meth)acrylate, (meth)acrylamide compound, N-vinyl-containing monomer, oxazoline monomer, (meth)acrylonitrile compound, etc. can be cited, but the present invention is not limited to the above examples. The nitrogen-containing monomer can be used alone or in combination of two or more. Among the nitrogen-containing monomers, piperidine monomer and nitrogen-containing (meth)acrylate are preferred from the aspects of improving the scratch resistance of the water-based ink, the adhesion to the substrate and the anti-blocking property.
[0027] It should be noted that, in the present invention, "(meth)acrylate" means "acrylate" or "methacrylate". "(Meth)acrylic acid" means "acrylic acid" or "methacrylic acid". "(Meth)acrylic acid" means "acrylic acid" or "methacrylic acid". In addition, "(meth)acryloyl" means "acryloyl" or "methacryloyl".
[0028] Examples of the piperidine monomer include piperidines containing a (meth)acryloyloxy group such as 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine, and 4-cyano-4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine; and piperidines containing a (meth)acryloyloxy group such as 4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloylamino-1,2,2,6,6-pentamethylpiperidine, and 4-cyano-4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine. Piperidines containing (meth)acryloylamino groups such as acylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine; piperidines containing butenoyl groups such as 4-butenoylamino-2,2,6,6-tetramethylpiperidine, 4-butenoyloxy-2,2,6,6-tetramethylpiperidine, 1-butenoyl-4-butenoyloxy-2,2,6,6-tetramethylpiperidine; piperidines containing (meth)acryloylalkoxy groups such as 4-(meth)acryloyl-1-methoxy-2,2,6,6-tetramethylpiperidine, etc., but the present invention is not limited to the above examples. The piperidine monomers can be used alone or in combination of two or more. Among the piperidine monomers, from the perspective of improving the scratch resistance of the aqueous ink, the adhesion to the substrate, and the blocking resistance, piperidine containing a (meth)acryloyloxy group and piperidine containing a (meth)acryloylamino group are preferred, piperidine containing a (meth)acryloyloxy group is more preferred, 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine and 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine are further preferred, and 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine is still more preferred.
[0029] Examples of the nitrogen atom-containing (meth)acrylate include those of formula (I):
[0030] [Chemistry 1]
[0031]
[0032] (Where R 1 represents a hydrogen atom or a methyl group, R 2 represents an alkylene group having 1 to 4 carbon atoms, R 3 and R 4 each independently represents an alkyl group having 1 to 4 carbon atoms)
[0033] The represented nitrogen-containing (meth)acrylate, morpholine ethylene oxide addition (meth)acrylate, etc. The nitrogen-containing (meth)acrylate can be used alone or in combination of two or more. The nitrogen-containing (meth)acrylate includes primary amine, secondary amine and tertiary amine. From the perspective of improving the scratch resistance of water-based ink, adhesion to substrates and anti-blocking properties, the nitrogen-containing (meth)acrylate is preferably a tertiary amine.
[0034] The nitrogen atom-containing (meth)acrylate represented by the formula (I) can be suitably used in the present invention from the viewpoint of improving the scratch resistance, adhesion to a substrate, and blocking resistance of the aqueous ink.
[0035] In formula (I), R 1 is a hydrogen atom or a methyl group. 2 is an alkylene group having 1 to 4 carbon atoms. Among the alkylene groups having 1 to 4 carbon atoms, methylene and ethylene are preferred from the viewpoint of improving the scratch resistance of the aqueous ink, the adhesion to the substrate, and the blocking resistance. 3 and R 4 Each independently represents an alkyl group having 1 to 4 carbon atoms. Among the alkyl groups having 1 to 4 carbon atoms, methyl and ethyl groups are preferred from the viewpoint of improving the scratch resistance of the aqueous ink, the adhesion to the substrate, and the blocking resistance.
[0036] Specific examples of the nitrogen-containing (meth)acrylate represented by formula (I) include dimethylaminoethyl (meth)acrylate, dimethylaminomethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminomethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, etc., but the present invention is not limited to the above examples. Among the nitrogen-containing (meth)acrylates, dimethylaminoethyl (meth)acrylate is preferred from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate and the blocking resistance.
[0037] As the (meth)acrylamide compound, for example, (meth)acrylamide, N-monomethyl (meth)acrylamide, N-monoethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-n-propyl (meth)acrylamide, N-isopropyl (meth)acrylamide, methylenebis (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, dimethylaminoethyl (meth)acrylamide, N,N-dimethylaminopropyl acrylamide, diacetone acrylamide, etc. can be cited, but the present invention is not limited to the above examples. The (meth)acrylamide compound can be used alone or in combination of two or more.
[0038] Examples of N-vinyl-containing monomers include N-vinylpyrrolidone, N-vinylpyridine, N-vinylimidazole, N-vinylpyrrole, N-vinyloxazolidinone, N-vinylsuccinimide, N-vinylmethylcarbamate, and N,N-methylvinylacetamide, but the present invention is not limited to the above examples. The N-vinyl-containing monomers may be used alone or in combination of two or more.
[0039] Examples of the oxazoline monomer include 2-isopropenyl-2-oxazoline and 2-vinyl-2-oxazoline, but the present invention is not limited to the above examples. The oxazoline monomers may be used alone or in combination of two or more.
[0040] Examples of the (meth)acrylonitrile compound include acrylonitrile and methacrylonitrile. Acrylonitrile and methacrylonitrile may be used alone or in combination.
[0041] From the perspective of improving the scratch resistance of the aqueous ink, adhesion to the substrate and blocking resistance, the content of the nitrogen atom-containing monomer in the monomer component is preferably 0.5 to 10 mass %, more preferably 1 to 5 mass %, further preferably 2 to 5 mass %, and even more preferably 3 to 5 mass %.
[0042] It should be noted that, from the perspective of improving the scratch resistance of water-based ink, the adhesion to the substrate and the blocking resistance, the emulsion particles preferably have two or more resin layers, and the monomer components constituting the outermost resin layer contain nitrogen-containing monomers. From the perspective of improving the scratch resistance of water-based ink, the adhesion to the substrate and the blocking resistance, the content of the nitrogen-containing monomer in the monomer components constituting the outermost resin layer is preferably 1 to 20% by mass, more preferably 2 to 10% by mass, further preferably 3 to 10% by mass, and further more preferably 5 to 10% by mass.
[0043] Monomers other than nitrogen atom-containing monomers can be used in the monomer component. As monomers other than nitrogen atom-containing monomers used in the monomer component, monofunctional monomers other than nitrogen atom-containing monomers and polyfunctional monomers other than nitrogen atom-containing monomers can be cited. Monofunctional monomers other than nitrogen atom-containing monomers and polyfunctional monomers other than nitrogen atom-containing monomers can be used alone or in combination. Among monofunctional monomers other than nitrogen atom-containing monomers and polyfunctional monomers other than nitrogen atom-containing monomers, it can be considered to use only polyfunctional monomers other than nitrogen atom-containing monomers in the monomer component. In the present invention, among monofunctional monomers other than nitrogen atom-containing monomers and polyfunctional monomers other than nitrogen atom-containing monomers, it is preferred to use only monofunctional monomers other than nitrogen atom-containing monomers, or to use monofunctional monomers other than nitrogen atom-containing monomers and polyfunctional monomers other than nitrogen atom-containing monomers in combination.
[0044] As representative examples of monofunctional monomers other than nitrogen-containing monomers, ethylenically unsaturated monofunctional monomers other than nitrogen-containing monomers can be cited. It should be noted that ethylenically unsaturated monofunctional monomers are monomers having one ethylenically unsaturated double bond. As ethylenically unsaturated monofunctional monomers other than nitrogen-containing monomers, for example, (meth) alkyl acrylates, hydroxyl-containing (meth) acrylates, (meth) arylalkyl acrylates, (meth) alkoxyalkyl acrylates, carboxyl-containing monomers, ketooxy-containing monomers, fluorine-containing monomers, styrene-based monomers, epoxy-containing monomers, silane-containing monomers, carbonyl-containing monomers, etc. can be cited, but the present invention is not limited to the above examples. The ethylenically unsaturated monofunctional monomers can be used alone or in combination of two or more.
[0045] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, tridecyl (meth)acrylate, n-lauryl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, 4-methylcyclohexylmethyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, and the like, but the present invention is not limited to the above examples. The alkyl (meth)acrylates may be used alone or in combination of two or more. Among the alkyl (meth)acrylates, from the viewpoint of improving the scratch resistance of the aqueous ink, the adhesion to the substrate and the blocking resistance, alkyl (meth)acrylates having an alkyl group with 1 to 12 carbon atoms are preferred, alkyl (meth)acrylates having an alkyl group with 1 to 8 carbon atoms are more preferred, and methyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate and cyclohexyl (meth)acrylate are still more preferred.
[0046] The content of the alkyl (meth)acrylate in the monomer component is preferably 40 to 98% by mass from the viewpoint of improving the scratch resistance, adhesion to a substrate, and blocking resistance of the aqueous ink.
[0047] As hydroxyl-containing (meth)acrylates, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone-modified hydroxy (meth)acrylate and the like, wherein the carbon number of the ester portion is 1 to 18, etc., but the present invention is not limited to the above examples. The hydroxyl-containing (meth)acrylates can be used alone or in combination of two or more. Among the hydroxyl-containing (meth)acrylates, from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate and the blocking resistance, hydroxyalkyl (meth)acrylates having 1 to 12 carbon atoms in the alkyl group are preferred, hydroxyalkyl (meth)acrylates having 1 to 8 carbon atoms in the alkyl group are more preferred, hydroxyalkyl (meth)acrylates having 1 to 4 carbon atoms in the alkyl group are further preferred, and 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are further preferred.
[0048] The content of the hydroxyl group-containing (meth)acrylate in the monomer component is preferably 0.5 to 30% by mass from the viewpoint of improving the scratch resistance of the aqueous ink, the adhesion to the substrate, and the blocking resistance.
[0049] Examples of the aralkyl (meth)acrylate include aralkyl (meth)acrylates having an aralkyl group having 7 to 18 carbon atoms, such as benzyl (meth)acrylate, phenylethyl (meth)acrylate, methylbenzyl (meth)acrylate, and naphthylmethyl (meth)acrylate, but the present invention is not limited to the above examples. These aralkyl (meth)acrylates may be used alone or in combination of two or more.
[0050] Examples of the alkoxyalkyl (meth)acrylate include methoxyethyl (meth)acrylate, methoxybutyl (meth)acrylate, ethoxybutyl (meth)acrylate, trimethylolpropane tripropoxy (meth)acrylate, etc., but the present invention is not limited to the above examples. The alkoxyalkyl (meth)acrylate may be used alone or in combination of two or more.
[0051] As the carboxyl-containing monomer, for example, (methyl) acrylic acid, maleic acid, fumaric acid, crotonic acid, itaconic acid, citraconic acid, maleic anhydride, maleic acid monomethyl ester, maleic acid monobutyl ester, itaconic acid monomethyl ester, itaconic acid monobutyl ester, vinyl benzoic acid, oxalic acid monohydroxyethyl (methyl) acrylate, carboxyl terminal caprolactone modified (methyl) acrylate, etc. can be enumerated, but the present invention is not limited to the above-mentioned illustration. The carboxyl-containing monomer can be used alone or in combination of two or more. Among the carboxyl-containing monomers, acrylic acid, methacrylic acid and itaconic acid are preferred from the aspect of improving the dispersion stability of the emulsion particles, and acrylic acid and methacrylic acid are more preferred.
[0052] Examples of keto group-containing monomers include ethylene glycol (meth)acrylate, ethylene glycol methoxy (meth)acrylate, diethylene glycol (meth)acrylate, diethylene glycol methoxy (meth)acrylate and other (di)ethylene glycol (methoxy) (meth)acrylates, but the present invention is not limited to the above examples. The keto group-containing monomers may be used alone or in combination of two or more.
[0053] As the fluorine-containing atom monomer, for example, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, perfluorobutyl ethyl (meth)acrylate, perfluoroisononyl ethyl (meth)acrylate, perfluorooctyl ethyl (meth)acrylate, etc., which contain fluorine atoms and alkyl (meth)acrylates, etc., can be cited, but the present invention is not limited to the above examples. The fluorine-containing atom monomers can be used alone or in combination of two or more.
[0054] Examples of the styrene-based monomers include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, o-tert-butylstyrene, m-tert-butylstyrene, p-tert-butylstyrene and other alkylstyrenes having 1 to 4 carbon atoms in the alkyl group, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-ethoxystyrene, m-ethoxystyrene, p-ethoxystyrene, o-tert-butoxystyrene, m-tert-butoxystyrene, p-tert-butoxystyrene and other alkoxystyrenes having 1 to 4 carbon atoms in the alkoxy group, o-fluorostyrene, m-fluorostyrene, p-fluorostyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, o-bromostyrene, m-bromostyrene, p-bromostyrene and other halogen-containing styrenes, o-acetoxystyrene, m-acetoxystyrene, p-acetoxystyrene and other acetoxystyrenes, and vinyltoluene, but the present invention is not limited to the above examples. These monomers may be used alone or in combination of two or more. Styrene monomers may have functional groups such as methyl, alkyl such as tert-butyl, nitro, nitrile, alkoxy, acyl, sulfone, hydroxyl, and halogen on the benzene ring. Among styrene monomers, styrene, alkylstyrenes having 1 to 4 carbon atoms in the alkyl group, and alkoxystyrenes having 1 to 4 carbon atoms in the alkoxy group are preferred from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate, and the blocking resistance. Styrene and alkylstyrenes having 1 to 4 carbon atoms in the alkyl group are more preferred. Styrene and alkylstyrenes having 1 to 4 carbon atoms in the alkyl group are further preferred. Styrene and alkylstyrenes having 1 or 2 carbon atoms in the alkyl group are further preferred. Styrene is even more preferred.
[0055] Examples of epoxy group-containing monomers include epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate, α-methyl glycidyl (meth)acrylate, glycidyl allyl ether, and 3,4-epoxy (cyclohexyl)methyl (meth)acrylate, but the present invention is not limited to the above examples. The monomers may be used alone or in combination of two or more.
[0056] Examples of the silyl group-containing monomer include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(methoxyethoxy)silane, γ-(meth)acryloxypropyl trimethoxysilane, 2-phenylethyl trimethoxysilane, vinyl trichlorosilane, γ-(meth)acryloxypropyl hydroxysilane, and γ-(meth)acryloxypropyl methylhydroxysilane, but the present invention is not limited to the above examples. The monomers may be used alone or in combination of two or more.
[0057] As the carbonyl group-containing monomer, for example, acrolein, formyl styrene, vinyl ethyl ketone, (meth) acryloxyalkyl acrolein, acetone (meth) acrylate, diacetone (meth) acrylate, 2-hydroxypropyl (meth) acrylate acetoacetate, butanediol-1,4-acrylate acetoacetate, (meth) acrylate oxycyclohexylmethyl ester, etc. can be cited, but the present invention is not limited to the above examples. The monomers can be used alone or in combination of two or more.
[0058] Representative examples of polyfunctional monomers other than nitrogen atom-containing monomers include ethylenically unsaturated polyfunctional monomers other than nitrogen atom-containing monomers. It should be noted that the ethylenically unsaturated polyfunctional monomer is a monomer having two or more ethylenically unsaturated double bonds.
[0059] Examples of the polyfunctional monomer other than the nitrogen atom-containing monomer include ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethylene oxide-modified 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, propylene oxide-modified neopentyl glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate. di(meth)acrylates of polyols having 1 to 10 carbon atoms, such as polyethylene glycol di(meth)acrylates having 2 to 50 moles of ethylene oxide, polypropylene glycol di(meth)acrylates having 2 to 50 moles of propylene oxide, tripropylene glycol di(meth)acrylates having 2 to 4 moles of alkylene oxide, and 2 to 50 moles of alkylene oxide added; ethoxylated glycerol tri(meth)acrylate The present invention also includes tri(meth)acrylates of polyhydric alcohols having 1 to 10 carbon atoms, such as tri(meth)acrylates of polyhydric alcohols having 1 to 10 carbon atoms, such as propylene oxide-modified glycerol tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol monohydroxy tri(meth)acrylate, and trimethylolpropane triethoxy tri(meth)acrylate; tetra(meth)acrylates of polyhydric alcohols having 1 to 10 carbon atoms, such as pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and ditrimethylolpropane tetra(meth)acrylate; penta(meth)acrylates of polyhydric alcohols having 1 to 10 carbon atoms, such as pentaerythritol penta(meth)acrylate and dipentaerythritol (monohydroxy) penta(meth)acrylate; and polyfunctional (meth)acrylates, such as hexa(meth)acrylates of polyhydric alcohols having 1 to 10 carbon atoms, such as pentaerythritol hexa(meth)acrylate, but are not limited to the above examples. The polyfunctional monomers may be used alone or in combination of two or more.
[0060] In the present invention, from the viewpoint of imparting ultraviolet absorbency to the emulsion particles, an ultraviolet absorbing monomer or the like may be contained in the monomer component within a range not hindering the purpose of the present invention.
[0061] From the perspective of obtaining an aqueous ink having excellent scratch resistance, adhesion to the substrate and blocking resistance, the monomer components preferably contain an alkyl (meth)acrylate, a hydroxyl (meth)acrylate and a styrene-based monomer, and more preferably contain an alkyl (meth)acrylate having an alkyl group with 1 to 8 carbon atoms, a hydroxyalkyl (meth)acrylate having an alkyl group with 2 to 4 carbon atoms and styrene.
[0062] From the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and blocking resistance, the content of the alkyl (meth)acrylate in the monomer component is preferably 35 to 85% by mass, and more preferably 40 to 80% by mass. From the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and blocking resistance, the content of the alkyl (meth)acrylate in which the carbon number of the alkyl group in the monomer component is 1 to 3, preferably methyl (meth)acrylate, is preferably 10 to 60% by mass, and more preferably 15 to 55% by mass. In addition, from the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and blocking resistance, the content of the alkyl (meth)acrylate in which the carbon number of the alkyl group in the monomer component is 4 to 8 is preferably 10 to 40% by mass, and more preferably 15 to 35% by mass.
[0063] From the viewpoint of improving the scratch resistance, adhesion to substrates and blocking resistance of the aqueous ink, the content of the hydroxyl group-containing (meth)acrylate in the monomer component is preferably 0.3 to 25% by mass, more preferably 0.5 to 20% by mass, and even more preferably 0.5 to 15% by mass.
[0064] From the viewpoint of improving the scratch resistance of the aqueous ink, the adhesion to the substrate, and the blocking resistance, the content of the styrene monomer in the monomer component is preferably 5 to 55% by mass, more preferably 10 to 50% by mass.
[0065] The monomer components may include carboxyl-containing monomers represented by (meth)acrylic acid, etc., but from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate and the blocking resistance, the content of the carboxyl-containing monomer in the monomer components is preferably 3% by mass or less, more preferably 1% by mass or less, and the lower limit is 0% by mass.
[0066] As a method for emulsion polymerization of monomer components, for example, there can be cited: a method in which an emulsifier is dissolved in an aqueous medium containing a water-soluble organic solvent such as a lower alcohol such as methanol and water, a medium such as water, and the monomer components and a polymerization initiator are added dropwise under stirring; a method in which the monomer components pre-emulsified with an emulsifier and water are added dropwise to water or an aqueous medium, etc., but the present invention is not limited to this method. It should be noted that the amount of the medium can be appropriately set in consideration of the amount of non-volatile components contained in the obtained resin emulsion. The medium can be pre-added to the reaction vessel, or it can be used in the form of a pre-emulsion. In addition, the medium can be used as needed when emulsion polymerization of the monomer components is carried out and a resin emulsion is prepared.
[0067] When the monomer components are subjected to emulsion polymerization, the emulsion polymerization may be carried out after the monomer components, emulsifier and medium are mixed; the monomer components, emulsifier and medium may be emulsified by stirring to prepare a pre-emulsion and then the emulsion polymerization may be carried out; or at least one of the monomer components, emulsifier and medium may be mixed with the pre-emulsion of the remaining components to carry out the emulsion polymerization. The monomer components, emulsifier and medium may be added at once, in batches, or continuously dropwise.
[0068] The resin emulsion is obtained by emulsion polymerization of the monomer components as described above. In the case where an outer layer is formed on the emulsion particles contained in the resin emulsion obtained above, the monomer components can be emulsion polymerized in the resin emulsion in the same manner as described above, thereby forming an outer layer on the emulsion particles. In addition, in the case where an outer layer is further formed on the emulsion particles having the outer layer formed thereon, the monomer components can be emulsion polymerized in the resin emulsion in the same manner as described above, thereby further forming an outer layer on the emulsion particles. In this way, a resin emulsion containing emulsion particles having a multilayer structure can be prepared by a multistage emulsion polymerization method.
[0069] Examples of the emulsifier include anionic emulsifiers, nonionic emulsifiers, cationic emulsifiers, amphoteric emulsifiers, polymer emulsifiers, etc. These emulsifiers may be used alone or in combination of two or more.
[0070] Examples of the anionic emulsifier include alkyl sulfates such as ammonium dodecyl sulfate and sodium dodecyl sulfate; alkyl sulfonates such as ammonium dodecyl sulfonate, sodium dodecyl sulfonate, and sodium alkyl diphenyl ether disulfonate; alkyl aryl sulfonates such as ammonium dodecylbenzene sulfonate and sodium dodecylnaphthalene sulfonate; polyoxyethylene alkyl sulfonates; polyoxyethylene alkyl sulfates; polyoxyethylene alkyl aryl sulfates; dialkyl sulfosuccinates; arylsulfonic acid-formaldehyde condensates; fatty acid salts such as ammonium laurate and sodium stearate; sulfates or salts thereof having an allyl group such as bis(polyoxyethylene polycyclic phenyl ether) (meth)acrylate sulfonate, propylene-alkyl sulfosuccinate, (meth)acrylate polyoxyethylene sulfonate, (meth)acrylate polyoxyethylene phosphate, and sulfonate of allyloxymethylalkyloxypolyoxyethylene; polyoxyethylene alkylphenyl ether sulfate ester salts, allyloxymethylalkoxyethylpolyoxyethylene sulfate ester salts, and polyoxyalkylene alkenyl ether sulfate ammonium salts. However, the present invention is not limited to the above examples.
[0071] Examples of the nonionic emulsifier include polyoxyethylene alkyl ethers, polyoxyethylene alkyl aryl ethers, condensates of polyethylene glycol and polypropylene glycol, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, fatty acid monoglycerides, condensates of ethylene oxide and aliphatic amines, allyloxymethylalkoxyethylhydroxypolyoxyethylene, and polyoxyalkylene alkenyl ethers, but the present invention is not limited to the above examples.
[0072] Examples of the cationic emulsifier include alkylammonium salts such as dodecylammonium chloride, but the present invention is not limited to the above examples.
[0073] Examples of the amphoteric emulsifier include betaine ester emulsifiers, but the present invention is not limited to the above examples.
[0074] Examples of polymer emulsifiers include poly(meth)acrylates such as sodium polyacrylate; polyvinyl alcohol; polyvinyl pyrrolidone; poly(meth)acrylate hydroxyalkyl esters such as polyhydroxyethyl acrylate; copolymers having one or more of the monomers constituting the polymer as copolymer components, etc., but the present invention is not limited to the above examples.
[0075] In addition, from the perspective of improving the scratch resistance, adhesion to the substrate and blocking resistance of the water-based ink, an emulsifier having a polymerizable group, i.e., a so-called reactive emulsifier, is preferred, and from the perspective of environmental protection, a non-nonylphenyl type emulsifier is preferred.
[0076] Examples of the reactive emulsifier include propylene-alkyl sulfosuccinate salts, (meth)acrylic acid polyoxyethylene sulfonate, polyoxyethylene alkyl propylene phenyl ether ammonium sulfate [for example, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., trade names: Aquaron HS-10, Aquaron BC-10, etc.], allyloxymethyl alkyloxy polyoxyethylene sulfonate [for example, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., trade name: Aquaron KH-10, etc.], allyloxymethyl nonylphenoxyethyl hydroxy polyoxyethylene sulfonate [for example, manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SE-10, etc.], allyloxymethyl alkoxyethyl hydroxy polyoxyethylene sulfate [for example, manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10, SR-20, SR-30, etc.], bis(polyoxyethylene polycyclic phenyl ether) methacrylate sulfonate [for example, manufactured by Nippon Emulsifier Co., Ltd., trade name: Antox MS-60, etc.], allyloxymethyl alkoxyethyl hydroxypolyoxyethylene [for example, manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap ER-10, ER-20, ER-30, ER-40, etc.], polyoxyethylene alkyl propenyl phenyl ether [for example, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., trade name: Aquaron RN-20, etc.], allyloxymethyl nonylphenoxyethyl hydroxypolyoxyethylene [for example, manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap NE-10, NE-20, NE-30, etc.], etc., but the present invention is not limited to the above examples. Each of the reactive emulsifiers may be used alone or in combination of two or more.
[0077] From the perspective of improving polymerization stability, the amount of the emulsifier is preferably 0.01 parts by mass or more, more preferably 0.5 parts by mass or more, and further preferably 1 part by mass or more per 100 parts by mass of the monomer component, and from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate, and the blocking resistance, it is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and further preferably 12 parts by mass or less. Therefore, from the perspective of improving polymerization stability, improving the scratch resistance of the water-based ink, the adhesion to the substrate, and the blocking resistance, the amount of the emulsifier is preferably 0.01 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, and further preferably 1 to 12 parts by mass per 100 parts by mass of the monomer component.
[0078] When the monomer components are polymerized, a polymerization initiator is preferably used. As the polymerization initiator, for example, azobisisobutyronitrile, 2,2-azobis(2-methylbutyronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(2-diaminopropane) hydrochloride, 4,4-azobis(4-cyanovaleric acid), 2,2-azobis(2-methylpropionamidine) and other azo compounds; persulfates such as potassium persulfate; peroxides such as hydrogen peroxide, benzoyl peroxide, p-chlorobenzoyl peroxide, lauroyl peroxide, ammonium peroxide, etc., but the present invention is not limited to the above examples. The polymerization initiators can be used alone or in combination of two or more.
[0079] From the perspective of increasing the polymerization rate and reducing the amount of residual unreacted monomers, the amount of the polymerization initiator per 100 parts by mass of the monomer component is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, and from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate, and the blocking resistance, it is preferably 1 part by mass or less, more preferably 0.8 parts by mass or less, and even more preferably 0.5 parts by mass or less. Therefore, from the perspective of increasing the polymerization rate, reducing the amount of residual unreacted monomers, and improving the scratch resistance of the water-based ink, the adhesion to the substrate, and the blocking resistance, the amount of the polymerization initiator per 100 parts by mass of the monomer component is preferably 0.01 to 1 part by mass, more preferably 0.05 to 0.8 parts by mass, and even more preferably 0.1 to 0.5 parts by mass.
[0080] The method for adding the polymerization initiator is not particularly limited. As its method for adding, for example, one-time feeding, batch feeding, continuous dripping etc. can be enumerated. In addition, from the aspect of accelerating the termination period of the polyreaction, a part of the polymerization initiator can be added before or after the monomer component ends the addition in the reaction system.
[0081] In order to promote the decomposition of the polymerization initiator, a suitable amount of a decomposing agent for the polymerization initiator, such as a reducing agent such as sodium hydrogen sulfite or a transition metal salt such as ferrous sulfate, may be added to the reaction system.
[0082] In order to adjust the molecular weight of the polymer constituting the emulsion particles, a chain transfer agent may be used in the monomer component. When a chain transfer agent is used in the monomer component, the molecular weight of the polymer constituting the emulsion particles can generally be reduced compared to when the chain transfer agent is not used in the monomer component.
[0083] As chain transfer agents, for example, 2-ethylhexyl thioglycolate, tert-dodecyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, thioglycolic acid, β-mercaptopropionic acid, 2-mercaptoethanol, α-methylstyrene, α-methylstyrene dimer, phosphorous acid, hypophosphorous acid, sodium hypophosphite, potassium hypophosphite, etc. can be cited, but the present invention is not limited to the above examples. The chain transfer agents can be used alone or in combination of two or more. From the perspective of adjusting the molecular weight of the polymer constituting the emulsion particles, the amount of the chain transfer agent is preferably 0.01 to 10 parts by mass per 100 parts by mass of the monomer component.
[0084] When the monomer components are polymerized, additives such as pH buffers, chelating agents, and film-forming aids may be added to the reaction system as needed. The amount of the additives varies depending on the type and cannot be determined uniformly. The amount of the additives is preferably about 0.01 to 5 parts by mass, more preferably about 0.1 to 3 parts by mass per 100 parts by mass of the monomer components.
[0085] The atmosphere for emulsion polymerization of the monomer components is not particularly limited, but is preferably an inert gas such as nitrogen from the viewpoint of improving the efficiency of the polymerization reaction.
[0086] The polymerization temperature when emulsion polymerizing the monomer components is not particularly limited, but is usually preferably 10 to 100° C., more preferably 40 to 95° C., and further preferably 50 to 60° C. The polymerization temperature may be constant or may be changed during the polymerization reaction.
[0087] The polymerization time for emulsion polymerization of the monomer components is not particularly limited and may be appropriately set depending on the progress of the polymerization reaction, but is generally about 2 to 8 hours.
[0088] It should be noted that when the monomer components are subjected to emulsion polymerization, a part or all of the acidic groups possessed by the obtained polymer may be neutralized using a neutralizing agent. The neutralizing agent may be used after the final addition of the monomer components, for example, between the first stage polymerization reaction and the second stage polymerization reaction, or at the end of the initial emulsion polymerization reaction.
[0089] As the neutralizing agent, for example, alkali metal hydroxides and alkaline earth metal hydroxides such as sodium hydroxide; alkali metal carbonates and alkaline earth metal carbonates such as calcium carbonate; ammonia; organic amines such as monomethylamine and other alkaline substances can be cited, but the present invention is not limited to the above examples. Among the neutralizing agents, volatile alkaline substances such as ammonia are preferred from the perspective of obtaining a water-based ink with excellent scratch resistance, adhesion to the substrate and blocking resistance. The neutralizing agent can be used in the form of an aqueous solution.
[0090] In addition, when the monomer components are subjected to emulsion polymerization, a silane coupling agent can be used in an appropriate amount from the aspects of improving the scratch resistance of the water-based ink, the adhesion to the substrate and the blocking resistance. As the silane coupling agent, for example, silane coupling agents having polymerizable unsaturated bonds such as (meth) acryloyl, vinyl, allyl, and acryl can be cited, but the present invention is not limited to the above examples.
[0091] By emulsion-polymerizing the monomer components as described above, a resin emulsion containing emulsion particles is obtained. The polymer constituting the emulsion particles may have a cross-linked structure.
[0092] The emulsion particles contained in the resin emulsion may have a single resin layer prepared by a single emulsion polymerization, or may have two or more resin layers prepared by a multi-stage emulsion polymerization. The emulsion particles having a single resin layer can be prepared by emulsion polymerization of the above-mentioned monomer components. In addition, the emulsion particles having two or more resin layers can be prepared by multi-stage emulsion polymerization, for example, emulsion polymerization of the monomer components forming the inner layer and emulsion polymerization of the monomer components forming the outer layer in the presence of the obtained emulsion particles, under the same polymerization method and polymerization conditions as when the above-mentioned monomer components are emulsion polymerized. In the case of forming an outer layer on the emulsion particles, from the aspect of forming a layer separation structure of the inner layer and the outer layer in the emulsion particles, it is preferred to emulsion polymerize the monomer components for forming the outer layer after the polymerization reaction rate when manufacturing the emulsion particles constituting the inner layer reaches 90% or more, preferably 95% or more.
[0093] From the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and anti-blocking properties, the number of resin layers constituting the emulsion particles is preferably 1 to 5 layers, more preferably 1 to 3 layers, further preferably 2 layers or 3 layers, and further more preferably 2 layers. From the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and anti-blocking properties, it is preferred that the emulsion particles have more than 2 resin layers. It should be noted that when the emulsion particles have more than 2 resin layers, the boundaries of the resin layers are not necessarily clear, and adjacent resin layers may be mixed with each other.
[0094] In emulsion particles having two or more resin layers, from the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and blocking resistance, among the resin layers constituting the emulsion particles, the resin layer with the highest glass transition temperature is preferably located on the inner side of the outermost layer.
[0095] In the emulsion particles having two resin layers, namely an inner layer and an outer layer, the mass ratio of the resin layer constituting the inner layer to the resin layer constituting the outer layer (resin layer constituting the inner layer / resin layer constituting the outer layer) is preferably 10 / 90 to 90 / 10, more preferably 20 / 80 to 80 / 20, further preferably 30 / 70 to 70 / 30, and further more preferably 40 / 60 to 60 / 40, from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate, and the blocking resistance. In the emulsion particles having three resin layers, namely an inner layer, an intermediate layer, and an outer layer, from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate, and the blocking resistance, the content of the resin layer constituting the inner layer is preferably 10 to 40% by mass, the content of the resin layer constituting the intermediate layer is preferably 20 to 60% by mass, and the content of the resin layer constituting the outer layer is preferably 20 to 60% by mass.
[0096] In the emulsion particles having a single resin layer, the glass transition temperature of the resin layer is preferably 0 to 50°C, more preferably 5 to 45°C, and further preferably 10 to 40°C, from the perspective of improving the scratch resistance of the aqueous ink, the adhesion to the substrate, and the blocking resistance.
[0097] In the emulsion particles having two resin layers, namely an inner layer and an outer layer, from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate and the blocking resistance, the glass transition temperature of the resin layer constituting the inner layer is preferably 60 to 120°C, more preferably 70 to 110°C, and further preferably 80 to 100°C, and the glass transition temperature of the resin layer constituting the outer layer is preferably -45 to 15°C, more preferably -40 to 10°C, and further preferably -35 to 5°C.
[0098] From the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and blocking resistance, the glass transition temperature of the entire emulsion particles having two or more resin layers is preferably -25 to 50° C., more preferably -20 to 45° C. From the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and blocking resistance, the glass transition temperature of the innermost resin layer of the emulsion particles having two or more resin layers is preferably 60 to 120° C., more preferably 70 to 110° C., and further preferably 80 to 100° C. The glass transition temperature of the innermost resin layer is preferably higher than the glass transition temperatures of other resin layers other than the innermost layer.
[0099] The glass transition temperature of the resin layer constituting the emulsion particles can be easily adjusted by adjusting the type and amount of the monomer used in the monomer component.
[0100] It should be noted that in this specification, the glass transition temperature (Tg) of the resin layer constituting the emulsion particles refers to the glass transition temperature of a homopolymer of a monomer used in the monomer component constituting the resin layer, based on the formula:
[0101] 1 / Tg=Σ(Wm / Tgm) / 100
[0102] [wherein, Wm represents the content (mass %) of monomer m in the monomer components constituting the resin layer, and Tgm represents the glass transition temperature (absolute temperature: K) of the homopolymer of monomer m]
[0103] The temperature obtained by the Fox equation represented.
[0104] In this specification, unless otherwise stated, the glass transition temperature of the polymer constituting the resin layer of the emulsion particles refers to the glass transition temperature obtained based on the above-mentioned Fox equation. The glass transition temperature of the entire resin layer constituting the emulsion particles having more than two resin layers refers to the glass transition temperature of the homopolymer of the monomer used in all the monomer components constituting all the resin layers used in the multi-stage emulsion polymerization, and the glass transition temperature obtained based on the above-mentioned Fox equation. It should be noted that for monomers such as special monomers and multifunctional monomers whose glass transition temperatures are unclear, when the total amount of the monomers whose glass transition temperatures are unclear in the monomer components is less than 10% by mass in terms of mass fraction, only the monomers whose glass transition temperatures have been determined are used to obtain the glass transition temperature. When the total amount of the monomers whose glass transition temperatures are unclear in the monomer components is greater than 10% by mass in terms of mass fraction, the glass transition temperature of the polymer is obtained by differential scanning calorimetry (DSC), differential calorimetry (DTA), thermomechanical analysis (TMA), etc.
[0105] Regarding the glass transition temperature of the polymer, for example, the homopolymer of methyl methacrylate is 105°C, the homopolymer of 2-ethylhexyl acrylate is -70°C, the homopolymer of n-butyl acrylate is -56°C, the homopolymer of n-butyl methacrylate is 20°C, the homopolymer of 2-hydroxyethyl methacrylate is 55°C, the homopolymer of acrylic acid is 95°C, the homopolymer of methacrylic acid is 130°C, the homopolymer of styrene is 100°C, the homopolymer of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine is 130°C, the homopolymer of 4-methacryloyloxy-1,2,2,6,6-pentamethylpiperidine is 130°C, the homopolymer of cyclohexyl methacrylate is 83°C, and the homopolymer of dimethylaminoethyl methacrylate is 18°C.
[0106] From the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and anti-blocking properties, the weight average molecular weight of the polymer constituting the resin layer of the emulsion particles is preferably 100,000 or more, more preferably 300,000 or more, further preferably 400,000 or more, and further more preferably 500,000 or more. Regarding the upper limit of the weight average molecular weight of the polymer, it is difficult to measure its weight average molecular weight when it has a cross-linked structure, so there is no special limitation. In the case of not having a cross-linked structure, from the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and anti-blocking properties, it is preferably 4 million or less. Therefore, from the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and anti-blocking properties, the weight average molecular weight of the polymer constituting the resin layer of the emulsion particles is preferably 100,000 to 4 million, more preferably 300,000 to 4 million, further preferably 400,000 to 4 million, and further more preferably 500,000 to 4 million.
[0107] The weight average molecular weight of the polymer constituting the resin layer of the emulsion particles refers to: the weight average molecular weight (in terms of polystyrene) obtained by using a gel chromatograph prepared using a gel chromatograph equipped with an RI (differential refractometer) detector [manufactured by Tosoh Corporation, model: HLC-8120GPC, columns: TSKgel G-5000HXL and TSKgel GMHXL-L used in series, developing solvent: tetrahydrofuran (THF)] and a calibration curve prepared using standard polystyrenes F-450, A-5000, A-1000 and A-300 manufactured by Tosoh Corporation.
[0108] Regarding the average particle size of the emulsion particles, from the perspective of improving the mechanical stability of the emulsion particles, it is preferably 50 nm or more, more preferably 100 nm or more, and from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate and the anti-blocking property, it is preferably 400 nm or less, more preferably 350 nm or less. Therefore, the average particle size of the emulsion particles is preferably 50 to 400 nm, more preferably 100 to 350 nm. It should be noted that in the present invention, the average particle size of the emulsion particles is a value based on the accumulation method measured using a particle size distribution measuring instrument based on the dynamic light scattering method [manufactured by Otsuka Electronics Co., Ltd., model: FPAR-1000].
[0109] The content of non-volatile components in the resin emulsion is preferably 10% by mass or more, more preferably 20% by mass or more, from the perspective of improving the productivity of water-based ink, and preferably 70% by mass or less, more preferably 60% by mass or less, from the perspective of improving the handling properties of water-based ink. Therefore, the content of non-volatile components in the resin emulsion is preferably 10 to 70% by mass, more preferably 20 to 60% by mass. In the present invention, the content of non-volatile components in the resin emulsion is obtained by weighing 1g of the resin emulsion, drying it at a temperature of 120°C for 1 hour using a hot air dryer, and taking the obtained dry residue as the non-volatile components, based on the formula:
[0110] [Content of non-volatile components in resin emulsion (mass %)]
[0111] =([Mass of dry residue]÷[1g of resin emulsion])×100
[0112] The value found.
[0113] The minimum film-forming temperature of the resin emulsion is preferably 80°C or less, more preferably 70°C or less, and further preferably 60°C or less from the perspective of improving adhesion to the substrate, and preferably -5°C or more, more preferably 5°C or more, and further preferably 10°C or more from the perspective of improving water resistance and blocking resistance. Therefore, the minimum film-forming temperature of the resin emulsion is preferably -5 to 80°C, more preferably 5 to 70°C, and further preferably 10 to 60°C. It should be noted that the minimum film-forming temperature of the resin emulsion refers to the temperature at which the resin emulsion is applied to a glass plate placed on a thermal gradient tester using an applicator to a thickness of 0.2 mm and dried to generate cracks.
[0114] The resin emulsion obtained as described above can be suitably used for the resin emulsion for aqueous ink of the present invention.
[0115] The resin emulsion for aqueous ink of the present invention can be easily prepared by mixing the resin emulsion and the carboxylic acid polymer non-metal salt.
[0116] In the present invention, the carboxylic acid polymer non-metallic salt is contained in the water-based ink resin emulsion, which is one of the characteristics of the present invention. The water-based ink resin emulsion of the present invention contains the carboxylic acid polymer non-metallic salt, so by using the water-based ink resin emulsion, it is possible to obtain a water-based ink having excellent scratch resistance, adhesion to a substrate, and blocking resistance.
[0117] Examples of carboxylic acid polymer salts include metal salts of carboxylic acid polymers such as sodium salts of carboxylic acid polymers. However, aqueous inks containing metal salts of carboxylic acid polymers have poor scratch resistance and blocking resistance, and therefore cannot solve the technical problems of the present invention.
[0118] In contrast, the resin emulsion for aqueous ink of the present invention contains a non-metallic salt of a carboxylic acid polymer. Therefore, unlike the case where a metal salt of a carboxylic acid polymer is used in the resin emulsion for aqueous ink, the use of the resin emulsion for aqueous ink of the present invention exhibits not only excellent adhesion to the substrate but also excellent scratch resistance and blocking resistance.
[0119] As a raw material of the carboxylic acid polymer non-metal salt, a carboxylic acid polymer is used. A carboxylic acid polymer refers to a polymer having a carboxyl group. For example, a carboxylic acid polymer can be obtained by polymerizing a monomer component containing an unsaturated carboxylic acid having a carboxyl group. Unsaturated carboxylic acids having a carboxyl group include monobasic acids and polybasic acids. Examples of monobasic acids include acrylic acid and methacrylic acid, but the present invention is not limited to the above examples. Examples of polybasic acids include maleic acid, fumaric acid, itaconic acid, etc., but the present invention is not limited to the above examples.
[0120] The monomer component containing the unsaturated carboxylic acid having a carboxyl group may be composed of only the unsaturated carboxylic acid having a carboxyl group, or may contain a free radical polymerizable monomer other than the unsaturated carboxylic acid having a carboxyl group within the scope that does not hinder the purpose of the present invention. As the free radical polymerizable monomer, for example, unsaturated carboxylic acid alkyl esters such as (meth) methyl acrylate, aromatic unsaturated compounds such as styrene, vinyl esters such as vinyl acetate, unsaturated nitrile compounds such as acrylonitrile, etc. can be cited, but the present invention is not limited to the above examples.
[0121] The carboxylic acid polymer can be obtained by polymerizing a monomer component containing an unsaturated carboxylic acid having a carboxyl group, and can also be easily obtained from commercial sources. Examples of the carboxylic acid polymer that can be easily obtained from commercial sources include Aqualic HL-415 manufactured by Nippon Shokubai Co., Ltd., Jurymer AC-10SL manufactured by Toagosei Co., Ltd., and Malialim AKM-0531 manufactured by NOF Corporation, but the present invention is not limited to the above examples.
[0122] The carboxylic acid polymer nonmetallic salt can be easily prepared by neutralizing the carboxyl group of the carboxylic acid polymer with a nonmetallic base. Examples of the nonmetallic salt include ammonium salts, organic ammonium salts, and amine salts, but the present invention is not limited to the above examples.
[0123] Examples of the organic ammonium salt include methylammonium salt, ethylammonium salt, dimethylammonium salt, diethylammonium salt, trimethylammonium salt, and triethylammonium salt, but the present invention is not limited to the above examples.
[0124] Examples of the amine salt include trimethylamine salts, triethylamine salts, tributylamine and other trialkylamine salts having an alkyl group with 1 to 4 carbon atoms, ethanolamine salts, diethanolamine salts, triethanolamine salts, monoisopropanolamine salts, diisopropanolamine salts, triisopropanolamine salts and other trialkanolamine salts having an alkanol group with 1 to 4 carbon atoms, hydroxyethyldiisopropanolamine salts, dihydroxyethylisopropanolamine salts, tetrakis(2-hydroxypropyl)ethylenediamine salts, penta(2-hydroxypropyl)diethylenetriamine salts and the like, but the present invention is not limited to the above examples.
[0125] Among the non-metallic salts, ammonium salts and amine salts are preferred from the viewpoint of improving the scratch resistance, adhesion to substrates and blocking resistance of the aqueous ink, and ammonium salts and trialkylamine salts having 1 to 4 carbon atoms are more preferred.
[0126] The weight average molecular weight of the carboxylic acid polymer nonmetallic salt is preferably 500 or more, more preferably 1000 or more, from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate and the blocking resistance, and is preferably 50000 or less, more preferably 20000 or less, from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate and the blocking resistance. Therefore, the weight average molecular weight of the carboxylic acid polymer nonmetallic salt is preferably 500 to 50000, more preferably 1000 to 20000. It should be noted that the weight average molecular weight of the carboxylic acid polymer nonmetallic salt is a weight average molecular weight obtained from a calibration curve of standard sodium polyacrylate using gel permeation chromatography.
[0127] The acid value of the carboxylic acid polymer nonmetal salt, more specifically the acid value of the nonvolatile component of the carboxylic acid polymer nonmetal salt is not particularly limited, but is preferably 300 to 600 mgKOH / g from the perspective of improving the scratch resistance of the water-based ink, the adhesion to the substrate, and the blocking resistance. The acid value of the carboxylic acid polymer nonmetal salt is expressed as the number of mg of potassium hydroxide required to neutralize 1 g of the carboxylic acid polymer nonmetal salt. The acid value of the carboxylic acid polymer nonmetal salt is a value measured according to the method described in JIS K0070.
[0128] The carboxylic acid polymer non-metallic salt can be obtained by neutralizing the carboxyl group of the carboxylic acid polymer with a non-metallic base, and can also be easily obtained from commercial sources. Examples of the carboxylic acid polymer non-metallic salt that can be easily obtained from commercial sources include the trade names of Aron A-30SL and Aron A-6114 manufactured by Toagosei Co., Ltd., and the trade names of SN Dispersant 5020, SN Dispersant 5023, and NOPCOSPERSE 6100 manufactured by SAN NOPCO Co., Ltd., but the present invention is not limited to the above examples.
[0129] From the perspective of improving the scratch resistance, adhesion to substrates and blocking resistance of the aqueous ink, the amount of the non-metallic carboxylic acid polymer salt is preferably 0.3 to 10 parts by mass, more preferably 1 to 5 parts by mass, per 100 parts by mass of the non-volatile component of the resin emulsion.
[0130] From the perspective of improving the scratch resistance of water-based ink, adhesion to the substrate and blocking resistance, the mass ratio of the nitrogen atom-containing monomer to the carboxylic acid polymer non-metal salt (nitrogen atom-containing monomer / carboxylic acid polymer non-metal salt) is preferably 1 / 99 to 99 / 1, more preferably 5 / to 95 / 5, further preferably 10 / 90 to 90 / 10, and further more preferably 10 / 50 to 50 / 10.
[0131] The water-based ink of the present invention comprises the above-mentioned water-based ink resin emulsion and a colorant. As the color tone of the colorant, for example, achromatic colors such as white, black, gray, and chromatic colors such as yellow, magenta, cyan, blue, red, orange, and green can be enumerated, but the present invention is not limited to the above-mentioned exemplification.
[0132] As coloring agents, pigments and dyes can be mentioned. Among coloring agents, pigments are preferred due to their excellent weather resistance. When a pigment is used as a coloring agent, the pigment can be used in the form of a pigment dispersion such as a paste. As pigments, organic pigments and inorganic pigments can be mentioned. Organic pigments and inorganic pigments can be used alone or in combination.
[0133] As organic pigments, for example, azo pigments such as benzidine and Hansa yellow; azomethine pigments; methine pigments; anthraquinone pigments; phthalocyanine pigments such as phthalocyanine blue; perindole pigments; perylene pigments; diketopyrrolopyrrole pigments; thioindigo pigments; iminoisoindoline pigments; iminoisoindoline pigments; quinacridone pigments such as quinacridone red and quinacridone violet; flavanthrene pigments; indanthrene pigments; anthraquinone pyrimidine pigments; carbazole pigments; monoaryl yellow; diaryl yellow; benzimidazolone yellow; tolyl orange; naphthol orange; quinophthalone pigments, etc., but the present invention is not limited to the above examples. The organic pigments can be used alone or in combination of two or more. As preferred organic pigments, for example, CI pigment yellow, CI pigment red, CI pigment orange, CI pigment violet, CI pigment blue, CI pigment green, etc. can be mentioned.
[0134] As inorganic pigments, for example, titanium dioxide, antimony trioxide, zinc white, zinc lithopone, lead white, red iron oxide, black iron oxide, iron oxide, chromium oxide green, carbon black, chrome yellow, molybdenum red, iron (III) ferrocyanide (Prussian blue), ultramarine, lead chromate, etc., represented by mica, clay, aluminum powder, talc, aluminum silicate, etc., flat pigments, calcium carbonate, magnesium hydroxide, aluminum hydroxide, barium sulfate, magnesium carbonate, etc., can be cited, but the present invention is not limited to the above examples. The inorganic pigments can be used alone or in combination of two or more.
[0135] From the perspective of improving the dispersion stability in water-based ink, the average particle size of the pigment is preferably 30 nm or more, more preferably 50 nm or more. From the perspective of preventing nozzle clogging and improving the ejection stability of water-based ink ejected from the nozzle head when used as an inkjet water-based ink, the average particle size is preferably 200 nm or less, more preferably 150 nm or less. Therefore, the average particle size of the pigment is preferably 30 to 200 nm, more preferably 50 to 150 nm. It should be noted that the average particle size of the pigment refers to the volume average particle size measured using a laser diffraction scattering particle size distribution measuring device [manufactured by Beckman Coulter, model: LS13320].
[0136] Examples of the dye include CI solvent black, CI solvent red, CI solvent yellow, CI solvent blue, CI solvent green, CI solvent orange, and CI solvent violet, but the present invention is not limited to the above examples.
[0137] From the perspective of fully coloring the printed characters or images formed by the water-based ink, the amount of the colorant is preferably 50 parts by mass or more, more preferably 100 parts by mass or more per 100 parts by mass of the non-volatile components of the resin emulsion for water-based ink, and from the perspective of forming a uniform coating film of the water-based ink, the amount of the colorant is preferably 300 parts by mass or less, more preferably 200 parts by mass or less. Therefore, the amount of the colorant is preferably 50 to 300 parts by mass, more preferably 100 to 200 parts by mass per 100 parts by mass of the non-volatile components of the resin emulsion for water-based ink.
[0138] It should be noted that the aqueous ink may contain a solvent such as water, a water-soluble organic solvent, or a mixed solvent of water and a water-soluble organic solvent in order to improve the dispersibility of the colorant in the aqueous ink.
[0139] Examples of the water-soluble organic solvent include polyols such as diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, 1,3-propanediol, glycerol, dipropylene glycol, and tripropylene glycol; ethylene glycol monoethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, and ethylene glycol monoisobutyl ether; diethylene glycol monoethers such as diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether, and diethylene glycol monoisobutyl ether; and propylene glycol monomethyl ether. , propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monoisopropyl ether, propylene glycol monobutyl ether, propylene glycol monoisobutyl ether and other propylene glycol monoethers; polyethylene glycol monomethyl ether, polyethylene glycol monoethyl ether, polyethylene glycol monopropyl ether, polyethylene glycol monoisopropyl ether, polyethylene glycol monobutyl ether, polyethylene glycol monoisobutyl ether and other polyethylene glycol monoethers; polypropylene glycol monomethyl ether, polypropylene glycol monoethyl ether, polypropylene glycol monopropyl ether, polypropylene glycol monoisopropyl ether, polypropylene glycol monobutyl ether, polypropylene glycol monoisobutyl ether and other polypropylene glycol monoethers, but the present invention is not limited to the above examples. The water-soluble organic solvent can be used alone or in combination of two or more. Among the water-soluble organic solvents, diethylene glycol, triethylene glycol, propylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether and diethylene glycol monoisobutyl ether are preferred.
[0140] The amount of the solvent described above varies depending on the type and amount of the colorant contained in the aqueous ink and cannot be determined without compromise. Therefore, it is preferably appropriately determined according to the type and amount of the colorant contained in the aqueous ink.
[0141] The content of the non-volatile component in the water-based ink of the present invention is preferably 20% by mass or more, more preferably 25% by mass or more, from the aspect of improving the productivity of the water-based ink, and is preferably 80% by mass or less, more preferably 70% by mass or less, from the aspect of improving the handling property of the water-based ink. Therefore, the content of the non-volatile component in the water-based ink of the present invention is preferably 20 to 80% by mass, more preferably 25 to 70% by mass. The non-volatile component amount of the water-based ink of the present invention is a value measured in the same manner as the non-volatile component amount of the above-mentioned resin emulsion.
[0142] The water-based ink of the present invention may contain resin emulsions other than the above-mentioned resin emulsion for water-based ink, water-soluble resins, water-dispersible resins and other resins within the range that does not hinder the purpose of the present invention. In addition, the water-based ink of the present invention may contain additives such as surfactants, film-forming aids, ultraviolet absorbers, ultraviolet inhibitors, fillers, leveling agents, dispersants, thickeners, wetting agents, plasticizers, stabilizers, antioxidants and the like in appropriate amounts within the range that does not hinder the purpose of the present invention.
[0143] The water-based ink of the present invention may contain a resin emulsion other than the above-mentioned resin emulsion for water-based ink, such as a polyurethane resin emulsion, an epoxy resin emulsion, or a polyester emulsion, from the viewpoint of improving adhesion to a substrate.
[0144] Examples of urethane resin emulsions include polyether polyurethane resin emulsions, polycarbonate polyurethane resin emulsions, polyester polyurethane resin emulsions, etc., but the present invention is not limited to the above examples. Examples of commercially available polyurethane resin emulsions include UCOAT UX-485 (polycarbonate polyurethane resin emulsion), UCOAT UWS-145 (polyester polyurethane resin emulsion), Parmalin UA-368T (polycarbonate polyurethane resin emulsion), Parmalin UA-200 (polyether polyurethane resin emulsion), UCOAT DA-100 (polyether polyurethane resin emulsion), UCOAT DA-200 (polyether polyurethane resin emulsion), etc., manufactured by Sanyo Chemical Industries, Ltd., but the present invention is not limited to the above examples. Examples of commercially available epoxy resin emulsions include ADEKA Resin series manufactured by ADEKA Co., Ltd., etc., but the present invention is not limited to the above examples. Examples of commercially available polyester emulsions include Elitel series manufactured by Unitika Co., Ltd. However, the present invention is not limited to the above examples.
[0145] In the present invention, the printed characters or images having a specific pattern can be formed, for example, by ejecting water-based ink in a specific pattern onto a substrate using an inkjet recording device, etc. A typical example of the substrate is a recording medium.
[0146] As the substrate (recording medium), for example, paper can be cited; paper (coated paper, etc.) laminated with a resin film such as polyethylene, polypropylene, polystyrene, etc.; metal plates such as aluminum, zinc, copper, etc.; resin films such as cellulose, polyethylene terephthalate, polyethylene, polystyrene, polypropylene, polycarbonate, polyvinyl acetal, polyvinyl chloride, acrylic resin, etc.; paper with a metal coating; resin film with a metal coating, etc., but the present invention is not limited to the above examples. Among the substrates (recording media), non-liquid-absorbing films are preferred. As non-liquid-absorbing films, for example, coated paper, polyester films such as polyethylene terephthalate (PET) films, polyvinyl chloride films, polypropylene films such as biaxially oriented polypropylene (OPP) films, polyethylene films, nylon films, etc. can be cited. Among the non-liquid-absorbing films, polyethylene terephthalate (PET) films and biaxially oriented polypropylene (OPP) films are preferred.
[0147] In the present invention, for example, a desired design can be imparted to a fiber product by printing a water-based ink on a fiber product such as cloth made of natural fibers such as cotton, or synthetic fibers such as polyester, acrylic, and polyamide using an inkjet recording device.
[0148] The water-based ink of the present invention obtained as described above has excellent scratch resistance, adhesion to substrates and blocking resistance, and can be appropriately used as inks such as water-based ink for inkjet, flexographic printing ink, offset printing ink, digital stencil printing ink, gravure printing ink, screen printing ink, etc. The water-based ink of the present invention can be particularly suitable for use as water-based ink for inkjet among these.
[0149] Example
[0150] Next, the present invention will be described in further detail based on examples, but the present invention is not limited to the examples.
[0151] Production Example 1
[0152] 112 g of pure water was placed (initial placement) in a 2.5 L (liter) stainless steel separable flask equipped with a reflux condenser, a stirrer, and a thermometer, and the temperature of the pure water was raised to the boiling point while stirring.
[0153] Next, when the pure water in the flask reached boiling point, the following operations were performed in the flask through independent supply paths under stirring in a boiling reflux state using the front end nozzle: 474 g of 80% acrylic acid aqueous solution was continuously dripped at a constant dripping speed for 180 minutes; 26 g of 15% sodium persulfate aqueous solution was continuously dripped at a constant dripping speed for 195 minutes; and 5.8 g of 45% sodium hypophosphite aqueous solution was continuously dripped at a constant dripping speed for 18 minutes, and then 28 g of the sodium hypophosphite aqueous solution was continuously dripped at a constant dripping speed for 192 minutes. In addition, when 92 minutes had passed from the start of polymerization, 97 g of pure water was continuously dripped into the flask from the front end nozzle at a constant dripping speed for 88 minutes using a supply path different from the above supply path.
[0154] When the addition of the acrylic acid aqueous solution was completed, the contents of the flask were kept (ripened) at boiling point reflux for 30 minutes to complete the reaction of the contents of the flask. After the reaction was completed, 62 g of a 45% sodium hypophosphite aqueous solution and 23 g of pure water were added to the flask, and 119 g of a 25% ammonia aqueous solution was slowly added dropwise to the flask while the contents of the flask were naturally cooled under stirring to neutralize the contents of the flask, thereby obtaining an acrylic acid polymer ammonium salt aqueous solution.
[0155] The acrylic acid polymer ammonium salt aqueous solution obtained above had a nonvolatile component (acrylic acid polymer ammonium salt) content of 45% by mass, and a weight average molecular weight of the acrylic acid polymer ammonium salt was 10,500.
[0156] It should be noted that the weight average molecular weight of the non-metallic carboxylic acid polymer salt is a weight average molecular weight obtained from a calibration curve of standard sodium polyacrylate using gel permeation chromatography.
[0157] Production Example 2
[0158] Into a 2.5 L (liter) stainless steel separable flask equipped with a reflux condenser, a stirrer, and a thermometer, 94 g of pure water was charged (initial charge), and the temperature of the pure water was raised to the boiling point while stirring.
[0159] Next, when the pure water in the flask reached boiling point, the following operations were performed in the flask through independent supply paths under stirring in a boiling reflux state: 474 g of 80% acrylic acid aqueous solution was continuously dripped at a constant dripping speed for 180 minutes; 26 g of 15% sodium persulfate aqueous solution was continuously dripped at a constant dripping speed for 195 minutes; and 5.8 g of 45% sodium hypophosphite aqueous solution was continuously dripped at a constant dripping speed for 18 minutes, and then 28 g of the sodium hypophosphite aqueous solution was continuously dripped at a constant dripping speed for 192 minutes. In addition, when 92 minutes had passed from the start of polymerization, 60 g of pure water was continuously dripped into the flask from the front nozzle at a constant dripping speed for 88 minutes using a supply path different from the above supply path.
[0160] When the addition of the acrylic acid aqueous solution was completed, the contents of the flask were kept (ripened) at boiling point reflux for 30 minutes to complete the reaction of the contents of the flask. After the reaction was completed, 62 g of a 45% sodium hypophosphite aqueous solution and 20 g of pure water were added to the flask, and 177 g of triethylamine was slowly added dropwise to the flask while the contents of the flask were naturally cooled under stirring to neutralize the contents of the flask, thereby obtaining an acrylic acid polymer triethylamine salt aqueous solution.
[0161] The acrylic acid polymer triethylamine salt aqueous solution obtained above had a nonvolatile component (acrylic acid polymer triethylamine salt) content of 45% by mass, and a weight average molecular weight of the acrylic acid polymer triethylamine salt was 10,500.
[0162] Comparative Manufacturing Example 1
[0163] 115 g of pure water was charged (initial charge) into a 2.5 L (liter) stainless steel separable flask equipped with a reflux condenser, a stirrer, and a thermometer, and the temperature of the pure water was raised to the boiling point while stirring.
[0164] Next, when the pure water in the flask reached boiling point, the following operations were performed in the flask through independent supply paths under stirring in a boiling reflux state: 474 g of 80% acrylic acid aqueous solution was continuously dripped at a constant dripping speed for 180 minutes; 26 g of 15% sodium persulfate aqueous solution was continuously dripped at a constant dripping speed for 195 minutes; and 5.8 g of 45% sodium hypophosphite aqueous solution was continuously dripped at a constant dripping speed for 18 minutes, and then 28 g of the sodium hypophosphite aqueous solution was continuously dripped at a constant dripping speed for 192 minutes. In addition, when 92 minutes had passed from the start of polymerization, 70 g of pure water was continuously dripped into the flask from the front nozzle at a constant dripping speed for 88 minutes using a supply path different from the above supply path.
[0165] When the addition of the acrylic acid aqueous solution was completed, the contents of the flask were kept (ripened) at boiling point reflux for 30 minutes to complete the reaction of the contents of the flask. After the reaction was completed, 62 g of a 45% sodium hypophosphite aqueous solution and 20 g of pure water were added to the flask, and 146 g of a 48% sodium hydroxide aqueous solution was slowly added dropwise to the flask while the contents of the flask were naturally cooled under stirring to neutralize the contents of the flask, thereby obtaining an acrylic acid polymer sodium salt aqueous solution.
[0166] The acrylic acid polymer sodium salt aqueous solution obtained above had a nonvolatile component (acrylic acid polymer sodium salt) content of 45% by mass, and a weight average molecular weight of the acrylic acid polymer sodium salt was 10,500.
[0167] Example 1
[0168] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 17 g of 2-ethylhexyl acrylate, and 483 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0169] After completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 235 g of 2-ethylhexyl acrylate, 235 g of methyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0170] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Production Example 1 was added to the flask under stirring, and filtered using a 300-mesh (JIS mesh, the same below) metal mesh to obtain a resin emulsion for water-based ink.
[0171] In addition, in each Example and each Comparative Example, pH is the value measured at 25 degreeC using the pH meter [manufactured by Horiba, Ltd., model: F-23].
[0172] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 620000. The glass transition temperature of the inner layer of the emulsion particles was 90° C., the glass transition temperature of the outer layer was −5° C., and the glass transition temperature of the emulsion particles themselves was 35° C.
[0173] Example 2
[0174] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 17 g of 2-ethylhexyl acrylate, and 483 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0175] After the completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 237 g of 2-ethylhexyl acrylate, 213 g of methyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 30 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer, and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0176] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0177] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 620000. The glass transition temperature of the inner layer of the emulsion particles was 90° C., the glass transition temperature of the outer layer was −5° C., and the glass transition temperature of the emulsion particles themselves was 35° C.
[0178] Example 3
[0179] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 17 g of 2-ethylhexyl acrylate, and 483 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0180] After the completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second-stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 238 g of 2-ethylhexyl acrylate, 192 g of methyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 50 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0181] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0182] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 620000. The glass transition temperature of the inner layer of the emulsion particles was 90° C., the glass transition temperature of the outer layer was −5° C., and the glass transition temperature of the emulsion particles themselves was 35° C.
[0183] Example 4
[0184] 766 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage dropping pre-emulsion consisting of 339 g of deionized water, 140 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 254 g of 2-ethylhexyl acrylate, 358 g of methyl methacrylate, 358 g of styrene, 20 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen-containing monomer was prepared in the dropping funnel, 30 g (corresponding to 2% by mass of the total amount of all monomer components) of the pre-emulsion was added to the flask, the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 30 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 120 minutes.
[0185] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0186] The nonvolatile content of the aqueous ink resin emulsion obtained above was 45% by mass, the average particle size of the emulsion particles contained in the aqueous ink resin emulsion was 220 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 430000. The glass transition temperature of the emulsion particles was 35°C.
[0187] Example 5
[0188] 766 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage dropping pre-emulsion consisting of 339 g of deionized water, 140 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 254 g of 2-ethylhexyl acrylate, 358 g of methyl methacrylate, 358 g of styrene, 20 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen-containing monomer was prepared in the dropping funnel, 30 g (corresponding to 2% by mass of the total amount of all monomer components) of the pre-emulsion was added to the flask, the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 30 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 120 minutes.
[0189] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the triethylamine salt of the carboxylic acid polymer obtained in Preparation Example 2 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0190] The nonvolatile content of the aqueous ink resin emulsion obtained above was 45% by mass, the average particle size of the emulsion particles contained in the aqueous ink resin emulsion was 220 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 430000. The glass transition temperature of the emulsion particles was 35°C.
[0191] Example 6
[0192] 766 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping was prepared in the dropping funnel, which consisted of 339 g of deionized water, 140 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 250 g of 2-ethylhexyl acrylate, 360 g of methyl methacrylate, 360 g of styrene, 20 g of 2-hydroxyethyl methacrylate, and 10 g of dimethylaminoethyl methacrylate as a nitrogen-containing monomer. 30 g of the pre-emulsion (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. The remainder of the pre-emulsion for dropping and 30 g of a 5% aqueous solution of ammonium persulfate were then uniformly dropped into the flask over 120 minutes.
[0193] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0194] The nonvolatile content of the aqueous ink resin emulsion obtained above was 45% by mass, the average particle size of the emulsion particles contained in the aqueous ink resin emulsion was 220 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 430000. The glass transition temperature of the emulsion particles was 35°C.
[0195] Example 7
[0196] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 68 g of deionized water, 28 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 7 g of 2-ethylhexyl acrylate, and 193 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0197] After the completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second-stage dropwise addition pre-emulsion consisting of 271 g of deionized water, 112 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 550 g of 2-ethylhexyl acrylate, 200 g of methyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 30 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0198] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0199] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 580000. The glass transition temperature of the inner layer of the emulsion particles was 89° C., the glass transition temperature of the outer layer was −36° C., and the glass transition temperature of the emulsion particles themselves was −18° C.
[0200] Example 8
[0201] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 68 g of deionized water, 28 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 7 g of 2-ethylhexyl acrylate, and 193 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0202] After the completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second-stage dropwise addition pre-emulsion consisting of 271 g of deionized water, 112 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 450 g of 2-ethylhexyl acrylate, 300 g of methyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 30 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer, and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0203] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0204] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 565000. The glass transition temperature of the inner layer of the emulsion particles was 89° C., the glass transition temperature of the outer layer was −19° C., and the glass transition temperature of the emulsion particles themselves was −3° C.
[0205] Example 9
[0206] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 17 g of 2-ethylhexyl acrylate, and 483 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0207] After the completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second-stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 240 g of 2-ethylhexyl acrylate, 160 g of methyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 80 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0208] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0209] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 210 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 620000. The glass transition temperature of the inner layer of the emulsion particles was 90°C, the glass transition temperature of the outer layer was -5°C, and the glass transition temperature of the emulsion particles themselves was 35°C.
[0210] Example 10
[0211] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 17 g of 2-ethylhexyl acrylate, and 483 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0212] After completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 235 g of 2-ethylhexyl acrylate, 235 g of methyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0213] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 115 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0214] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a two-layered resin layer, the average particle size of the emulsion particles was 210 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 530000. The glass transition temperature of the inner layer of the emulsion particles was 90°C, the glass transition temperature of the outer layer was -5°C, and the glass transition temperature of the emulsion particles themselves was 35°C.
[0215] Embodiment 11
[0216] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 17 g of 2-ethylhexyl acrylate, and 483 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0217] After completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 235 g of 2-ethylhexyl acrylate, 235 g of methyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0218] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 230 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0219] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 210 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 500000. The glass transition temperature of the inner layer of the emulsion particles was 90° C., the glass transition temperature of the outer layer was −5° C., and the glass transition temperature of the emulsion particles themselves was 35° C.
[0220] Example 12
[0221] 766 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first stage dropping pre-emulsion consisting of 339 g of deionized water, 140 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 254 g of 2-ethylhexyl acrylate, 358 g of methyl methacrylate, 358 g of styrene, 20 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-1,2,2,6,6-pentamethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-82] as a nitrogen atom-containing monomer was prepared in the dropping funnel, 30 g (corresponding to 2% by mass of the total amount of all monomer components) of the pre-emulsion was added to the flask, the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 30 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 120 minutes.
[0222] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0223] The nonvolatile content of the aqueous ink resin emulsion obtained above was 45% by mass, the average particle size of the emulsion particles contained in the aqueous ink resin emulsion was 220 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 430000. The glass transition temperature of the emulsion particles was 35°C.
[0224] Example 13
[0225] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 17 g of 2-ethylhexyl acrylate, and 483 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0226] After completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 217 g of 2-ethylhexyl acrylate, 253 g of cyclohexyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0227] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0228] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 620000. The glass transition temperature of the inner layer of the emulsion particles was 90° C., the glass transition temperature of the outer layer was −5° C., and the glass transition temperature of the emulsion particles themselves was 35° C.
[0229] Embodiment 14
[0230] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping was prepared in the dropping funnel, which consisted of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 15 g of 2-ethylhexyl acrylate, 370 g of methyl methacrylate, and 115 g of cyclohexyl methacrylate. 30 g of the pre-emulsion (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. The remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were then uniformly dropped into the flask over 120 minutes.
[0231] After completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 217 g of 2-ethylhexyl acrylate, 253 g of cyclohexyl methacrylate, 20 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0232] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0233] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 620000. The glass transition temperature of the inner layer of the emulsion particles was 90° C., the glass transition temperature of the outer layer was −5° C., and the glass transition temperature of the emulsion particles themselves was 35° C.
[0234] Embodiment 15
[0235] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 17 g of 2-ethylhexyl acrylate, and 483 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0236] After the completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second-stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 224 g of 2-ethylhexyl acrylate, 186 g of methyl methacrylate, 80 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0237] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0238] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 620000. The glass transition temperature of the inner layer of the emulsion particles was 90° C., the glass transition temperature of the outer layer was −5° C., and the glass transition temperature of the emulsion particles themselves was 35° C.
[0239] Example 16
[0240] 767 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 17 g of 2-ethylhexyl acrylate, and 483 g of styrene was prepared in the dropping funnel, 30 g of which (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 20 g of a 5% aqueous solution of ammonium persulfate were uniformly dropped into the flask over 120 minutes.
[0241] After the completion of the dropwise addition, the contents of the flask were maintained at 80° C. for 60 minutes, and then a second-stage dropwise addition pre-emulsion consisting of 169 g of deionized water, 70 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 203 g of 2-ethylhexyl acrylate, 87 g of methyl methacrylate, 200 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer and 10 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 60 minutes.
[0242] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0243] The content of nonvolatile components in the resin emulsion for water-based ink obtained above was 45% by mass, the emulsion particles contained in the resin emulsion for water-based ink had a resin layer with a two-layer structure, the average particle size of the emulsion particles was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 620000. The glass transition temperature of the inner layer of the emulsion particles was 90° C., the glass transition temperature of the outer layer was −5° C., and the glass transition temperature of the emulsion particles themselves was 35° C.
[0244] Embodiment 17
[0245] To the aqueous ink resin emulsion obtained in Example 1, 833 g of a urethane resin emulsion [manufactured by Sanyo Chemical Industries, Ltd., trade name: Parmalin UA-200] was added with stirring, and the mixture was filtered through a 300-mesh metal mesh to obtain an aqueous ink resin emulsion A.
[0246] The content of nonvolatile components in the resin emulsion A for aqueous ink obtained above was 40% by mass, the average particle size of the emulsion particles was 150 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 500,000.
[0247] Embodiment 18
[0248] To the resin emulsion for aqueous ink obtained in Example 1, 500 g of epoxy emulsion [manufactured by ADEKA Corporation, trade name: ADEKA Resin EM-0427WC] was added with stirring, and the mixture was filtered through a 300-mesh metal mesh to obtain a resin emulsion B for aqueous ink.
[0249] The content of nonvolatile components in the aqueous ink resin emulsion B obtained above was 46% by mass, the average particle size of the emulsion particles was 270 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 500,000.
[0250] Embodiment 19
[0251] To the aqueous ink resin emulsion obtained in Example 1, 833 g of a polyester emulsion [product name: Elitel KT-9204, manufactured by Unitika Co., Ltd.] was added with stirring, and the mixture was filtered through a 300-mesh metal mesh to obtain an aqueous ink resin emulsion C.
[0252] The content of nonvolatile components in the resin emulsion C for aqueous ink obtained above was 40% by mass, the average particle size of the emulsion particles was 200 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 500,000.
[0253] Comparative Example 1
[0254] 766 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage pre-emulsion for dropping was prepared in the dropping funnel, which consisted of 339 g of deionized water, 140 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Co., Ltd., trade name: Adeka Reasoap SR-10], 254 g of 2-ethylhexyl acrylate, 363 g of methyl methacrylate, 363 g of styrene, and 20 g of 2-hydroxyethyl methacrylate. 30 g of the pre-emulsion (equivalent to 2% by mass of the total amount of all monomer components) was added to the flask, and the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. The remainder of the pre-emulsion for dropping and 30 g of a 5% aqueous solution of ammonium persulfate were then uniformly dropped into the flask over 120 minutes.
[0255] After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer ammonium salt obtained in Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0256] The nonvolatile content of the aqueous ink resin emulsion obtained above was 45% by mass, the average particle size of the emulsion particles contained in the aqueous ink resin emulsion was 200 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 380000. The glass transition temperature of the emulsion particles was 35°C.
[0257] Comparative Example 2
[0258] 766 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first-stage dropping pre-emulsion consisting of 339 g of deionized water, 140 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 254 g of 2-ethylhexyl acrylate, 358 g of methyl methacrylate, 358 g of styrene, 20 g of 2-hydroxyethyl methacrylate, and 10 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen-containing monomer was prepared in the dropping funnel, 30 g (corresponding to 2% by mass of the total amount of all monomer components) of the pre-emulsion was added to the flask, the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 30 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 120 minutes.
[0259] After the addition was completed, the contents of the flask were maintained at 80° C. for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer sodium salt obtained in Comparative Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0260] The nonvolatile content of the aqueous ink resin emulsion obtained above was 45% by mass, the average particle size of the emulsion particles contained in the aqueous ink resin emulsion was 200 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 380000. The glass transition temperature of the emulsion particles was 35°C.
[0261] Comparative Example 3
[0262] 766 g of deionized water was placed in a flask equipped with a dropping funnel, a stirrer, a nitrogen inlet tube, a thermometer, and a reflux condenser. A first stage dropping pre-emulsion consisting of 339 g of deionized water, 140 g of a 25% aqueous solution of an emulsifier [manufactured by ADEKA Corporation, trade name: Adeka Reasoap SR-10], 258 g of 2-ethylhexyl acrylate, 336 g of methyl methacrylate, 336 g of styrene, 20 g of 2-hydroxyethyl methacrylate, and 50 g of 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine [manufactured by ADEKA Corporation, trade name: ADKSTAB LA-87] as a nitrogen atom-containing monomer was prepared in the dropping funnel, 30 g (corresponding to 2% by mass of the total amount of all monomer components) of the pre-emulsion was added to the flask, the temperature was raised to 80° C. while nitrogen was slowly blown, and 30 g of a 5% aqueous solution of ammonium persulfate was added to initiate polymerization. Thereafter, the remainder of the pre-emulsion for dropping and 30 g of a 5% aqueous ammonium persulfate solution were uniformly dropped into the flask over 120 minutes.
[0263] After the addition was completed, the contents of the flask were maintained at 80° C. for 60 minutes, and the pH was adjusted to 9 by adding 25% ammonia water to terminate the polymerization reaction. After the obtained reaction solution was cooled to room temperature, 23 g of the carboxylic acid polymer sodium salt obtained in Comparative Preparation Example 1 was added to the flask under stirring, and filtered with a 300-mesh metal mesh to obtain a resin emulsion for water-based ink.
[0264] The nonvolatile content of the aqueous ink resin emulsion obtained above was 45% by mass, the average particle size of the emulsion particles contained in the aqueous ink resin emulsion was 240 nm, and the weight average molecular weight of the polymer constituting the emulsion particles was 380000. The glass transition temperature of the emulsion particles was 35°C.
[0265] Next, a water-based ink was prepared according to the following method using the water-based ink resin emulsion obtained in each Example or each Comparative Example.
[0266] (1) Preparation of water-based ink
[0267] 22 g of the aqueous ink resin emulsion obtained in each example or comparative example was mixed with a homogenizer at a rotation speed of 1000 min. -1 While stirring, add 23 g of white paste, 10 g of propylene glycol, 15 g of diethylene glycol monoisopropyl ether, 0.4 g of polyether modified silicone surfactant [manufactured by Shin-Etsu Chemical Co., Ltd., model: KF-6011], and ion exchange water to make a total of 100 g, and after further stirring for 30 minutes, filter with a filter with an average pore size of 3 μm [manufactured by ADVANTEC Co., Ltd., model: MCP-3-C10S] to obtain a water-based ink.
[0268] It should be noted that the white paste was prepared as follows: 428 g of deionized water, 50 g of a dispersant [manufactured by Daiichi Kogyo Seiyaku Co., Ltd., trade name: Discoat N-14], 60 g of propylene glycol, 1000 g of titanium oxide [manufactured by Ishihara Sangyo Co., Ltd., model: CR-95, average particle size: 0.28 μm] and 200 g of glass beads (diameter: 1 mm) as a dispersion medium were mixed in a homogenizer at a rotation speed of 3000 min / min. -1 After dispersion at room temperature for 120 minutes, the mixture was filtered through a 300-mesh metal mesh to prepare a white paste.
[0269] (2) Production of inkjet printed products
[0270] Aqueous ink was filled into a printing evaluation device [manufactured by Genesis Corporation] equipped with an inkjet print head [manufactured by Kyocera Corporation, model: KJ4B-YH06WST-STDV] in air at a temperature of 25±1° C. and a relative humidity of 30±5%.
[0271] Next, in the printing evaluation device, the nozzle voltage was set to 26V, the frequency was set to 4kHz, the ejection droplet volume was set to 12pL (picoliter), the nozzle temperature was set to 32°C, the resolution was set to 600dpi, and the negative pressure was set to -4.0kPa. As a recording medium, a corona-treated polyester film [manufactured by Futamura Chemical Co., Ltd., trade name: TAIKO Polyester Film FE2001] was used, and the corona-treated polyester film was fixed on the conveying table so that the longitudinal direction and the conveying direction were the same direction. The printing command was transmitted to the above-mentioned printing evaluation device, and a solid image was printed on the corona-treated polyester film by an inkjet recording method with an aqueous ink at a 100% ejection volume (12pL, 600×600dpi), and the corona-treated polyester film was immediately dried for 10 seconds in a 100°C dryer to obtain a test sheet.
[0272] The following physical properties were investigated using the aqueous ink obtained in each example or each comparative example and the test piece obtained above. The results are shown in Table 1.
[0273] (1) Scratch resistance
[0274] The printed image on the test sheet was subjected to a pencil hardness test in accordance with JIS K5600, and the scratch resistance was evaluated based on the following evaluation criteria.
[0275] [Evaluation criteria]
[0276] 5: Pencil hardness is F or above
[0277] 4: Pencil hardness is HB
[0278] 3: Pencil hardness is B
[0279] 2: Pencil hardness is 2B
[0280] 1: Pencil hardness is 3B
[0281] 0: Pencil hardness is 4B or less
[0282] (2) Anti-adhesion
[0283] A polyester film which had not been subjected to corona treatment was stacked on the printed surface of the test sheet, and a force of 2 N / cm2 was applied to the polyester film in air at 25°C for 1 hour. 2 After a load of 1000 was applied, the polyester film was quickly peeled off, and the resistance at that time was observed. The blocking resistance was evaluated based on the following evaluation criteria.
[0284] [Evaluation criteria]
[0285] 5: No resistance was felt at all when the polyester film was peeled off.
[0286] 4: Only minimal resistance was felt when peeling off the polyester film.
[0287] 3: Only slight resistance was felt when peeling off the polyester film.
[0288] 2: When peeling off the polyester film, resistance is clearly felt.
[0289] 1: Strong resistance was felt when peeling off the polyester film.
[0290] 0: Resistance is very strongly felt when the polyester film is peeled off.
[0291] (3) Adhesion
[0292] The printed image on the test sheet was rubbed with a fingernail, and the adhesion to the substrate was evaluated based on the following evaluation criteria.
[0293] [Evaluation criteria]
[0294] 5: Even when the printed image was rubbed with fingernails, no peeling occurred.
[0295] 4: When the printed image is rubbed with fingernails, there is only minimal peeling of the image.
[0296] 3: When the printed image is rubbed with fingernails, the image peels off slightly.
[0297] 2: When the printed image is rubbed with fingernails, the image peels off slightly.
[0298] 1: When the printed image is rubbed with the fingernail, the image peels off obviously.
[0299] 0: When the printed image is rubbed with the nail of a finger, the image is easily peeled off.
[0300] (4) Comprehensive evaluation
[0301] The total value of the scores of each test item was used as an index for comprehensive evaluation.
[0302] [Table 1]
[0303]
[0304] As shown in the results in Table 1, the water-based inks obtained in the examples all achieved comprehensive excellence in scratch resistance, blocking resistance and adhesion compared with the water-based inks obtained in the comparative examples.
[0305] Industrial Applicability
[0306] The aqueous ink of the present invention has excellent comprehensive viscosity change stability, scratch resistance, blocking resistance and adhesion, and can therefore be appropriately used in industrial inks such as printing inks that form desired information, patterns, colors, etc., such as text, on substrates made of materials such as paper, resin sheets or resin films, metal plates, wood boards, leather, etc. using inkjet printing, flexographic printing, offset printing, digital stencil printing, gravure printing, screen printing, ink ribbons, etc.
Claims
1. A resin emulsion for water-based ink, which is a resin emulsion used in water-based ink, wherein the recording medium used for the water-based ink is a non-liquid-absorbing film, characterized in that: The resin emulsion contains emulsion particles and a carboxylic acid polymer non-metallic salt. The emulsion particles contain a polymer. The polymer includes a monomer component containing a nitrogen atom-containing monomer. The content of the nitrogen atom-containing monomer in the monomer component is 0.5% by mass to 10% by mass. As the carboxylic acid polymer non-metallic salt, a carboxylic acid polymer non-metallic salt with a weight average molecular weight of 500 to 50,000 is used. The mass ratio of the nitrogen atom-containing monomer to the carboxylic acid polymer non-metallic salt, i.e., the nitrogen atom-containing monomer / carboxylic acid polymer non-metallic salt is 10 / 90 to 90 / 10. The nitrogen atom-containing monomer contains a piperidine monomer. The amount of the carboxylic acid polymer non-metallic salt is 0.3 parts by mass to 10 parts by mass per 100 parts by mass of the non-volatile component of the resin emulsion. The non-liquid-absorbing film is coated paper, polyester film, polyvinyl chloride film, polypropylene film, polyethylene film or nylon film.
2. The resin emulsion for aqueous ink according to claim 1, wherein The nitrogen atom-containing monomer further contains at least one selected from the group consisting of nitrogen atom-containing (meth)acrylates, (meth)acrylamide compounds, N-vinyl group-containing monomers, oxazoline monomers, and (meth)acrylonitrile compounds.
3. The resin emulsion for aqueous ink according to claim 1, wherein The nitrogen atom-containing monomer further includes a nitrogen atom-containing (meth)acrylate.
4. The resin emulsion for aqueous ink according to claim 1, wherein The piperidine monomer is at least one selected from the group consisting of piperidine containing a (meth)acryloyloxy group and piperidine containing a (meth)acryloylamino group.
5. The aqueous ink resin emulsion according to any one of claims 1 to 4, wherein The monomer component contains an alkyl (meth)acrylate.
6. The resin emulsion for aqueous ink according to claim 5, wherein The alkyl (meth)acrylate is an alkyl (meth)acrylate in which the alkyl group has 1 to 18 carbon atoms.
7. The resin emulsion for aqueous ink according to claim 5, wherein: The content of the alkyl (meth)acrylate in the monomer component is 40% by mass to 98% by mass.
8. The resin emulsion for aqueous ink according to claim 5, wherein The content of the (meth)acrylic acid alkyl ester in which the alkyl group has 1 to 3 carbon atoms in the monomer component is 10% by mass to 60% by mass.
9. The resin emulsion for aqueous ink according to claim 5, wherein: The content of the alkyl (meth)acrylate having an alkyl group with 4 to 8 carbon atoms in the monomer component is 10% by mass to 40% by mass.
10. The resin emulsion for aqueous ink according to any one of claims 1 to 4, wherein The monomer component contains a hydroxyl group-containing (meth)acrylate.
11. The resin emulsion for aqueous ink according to claim 5, wherein The monomer component contains a hydroxyl group-containing (meth)acrylate.
12. The resin emulsion for aqueous ink according to any one of claims 6 to 9, wherein The monomer component contains a hydroxyl group-containing (meth)acrylate.
13. The resin emulsion for aqueous ink according to claim 10, wherein The hydroxyl group-containing (meth)acrylate is a hydroxyl group-containing (meth)acrylate having 1 to 18 carbon atoms in the ester portion.
14. The resin emulsion for aqueous ink according to claim 10, wherein The content of the hydroxyl group-containing (meth)acrylate in the monomer component is 0.5% by mass to 30% by mass.
15. The resin emulsion for aqueous ink according to any one of claims 1 to 4, wherein The monomer component contains a carboxyl group-containing monomer.
16. The resin emulsion for aqueous ink according to claim 15, wherein The carboxyl group-containing monomer is at least one selected from the group consisting of acrylic acid, methacrylic acid, and itaconic acid.
17. The resin emulsion for aqueous ink according to claim 15, wherein The content of the carboxyl group-containing monomer in the monomer components is 3% by mass or less.
18. The resin emulsion for aqueous ink according to any one of claims 1 to 4, wherein The monomer component contains a styrene-based monomer.
19. The resin emulsion for aqueous ink according to claim 18, wherein The content of the styrene-based monomer in the monomer component is 5% by mass to 55% by mass.
20. The aqueous ink resin emulsion according to any one of claims 1 to 4, wherein The carboxylic acid polymer used as a raw material of the non-metallic carboxylic acid polymer salt is a polymer obtained by polymerizing a monomer component containing an unsaturated carboxylic acid having a carboxyl group.
21. The resin emulsion for aqueous ink according to claim 20, wherein: The unsaturated carboxylic acid having a carboxyl group is a monobasic acid or a polybasic acid.
22. The aqueous ink resin emulsion according to any one of claims 1 to 4, wherein The non-metallic salt of the non-metallic salt of the carboxylic acid polymer is an ammonium salt.
23. The resin emulsion for aqueous ink according to any one of claims 1 to 4, wherein The non-metallic salt of the non-metallic salt of the carboxylic acid polymer is an organic ammonium salt.
24. The resin emulsion for aqueous ink according to any one of claims 1 to 4, wherein The non-metallic salt of the non-metallic salt of the carboxylic acid polymer is an amine salt.
25. The resin emulsion for aqueous ink according to any one of claims 1 to 4, wherein The number of resin layers constituting the emulsion particles is 1 to 5.
26. The resin emulsion for aqueous ink according to claim 25, wherein The emulsion particles have a single resin layer, and the glass transition temperature of the resin layer is 0°C to 50°C.
27. The resin emulsion for aqueous ink according to claim 25, wherein The emulsion particles have 2 to 5 resin layers.
28. The resin emulsion for aqueous ink according to claim 27, wherein The glass transition temperature of the entire emulsion particles having 2 to 5 resin layers is -25°C to 50°C.
29. The resin emulsion for aqueous ink according to claim 27, wherein The monomer component constituting the outermost resin layer among the two to five resin layers included in the emulsion particles includes a nitrogen atom-containing monomer.
30. The resin emulsion for aqueous ink according to claim 29, wherein The content of the nitrogen atom-containing monomer in the monomer components constituting the outermost resin layer is 1% by mass to 20% by mass.
31. The aqueous ink resin emulsion according to any one of claims 27 to 30, wherein The emulsion particles have two resin layers, an inner layer and an outer layer, and the mass ratio of the resin layer constituting the inner layer to the resin layer constituting the outer layer, that is, the resin layer constituting the inner layer / the resin layer constituting the outer layer is 10 / 90 to 90 / 10.
32. The aqueous ink resin emulsion according to any one of claims 27 to 30, wherein The emulsion particles have two resin layers, an inner layer and an outer layer. The glass transition temperature of the resin layer constituting the inner layer is 60°C to 120°C, and the glass transition temperature of the resin layer constituting the outer layer is -45°C to 15°C.
33. The resin emulsion for aqueous ink according to any one of claims 1 to 4, wherein The average particle size of the emulsion particles is 50nm to 400nm.
34. The resin emulsion for aqueous ink according to any one of claims 1 to 4, wherein The content of the nonvolatile component in the resin emulsion is 10% by mass to 70% by mass.
35. A water-based ink comprising the resin emulsion for water-based ink according to any one of claims 1 to 34 and a colorant.
36. Aqueous ink as claimed in claim 35, wherein: The colorant contains at least one pigment selected from the group consisting of organic pigments and inorganic pigments.
37. Aqueous ink as claimed in claim 36, wherein: The average particle size of the pigment is 30nm to 200nm.
38. Aqueous ink as claimed in claim 36, wherein, The inorganic pigment is titanium dioxide.
39. The aqueous ink according to any one of claims 35 to 38, wherein Contains water-soluble organic solvents.
40. The aqueous ink of claim 39, wherein: The water-soluble organic solvent is at least one selected from the group consisting of polyols, ethylene glycol monoether, diethylene glycol monoether, propylene glycol monoether, polyethylene glycol monoether, and polypropylene glycol monoether.
41. The aqueous ink according to any one of claims 35 to 38, wherein The content of the nonvolatile component in the aqueous ink is 20% by mass to 80% by mass.
42. The aqueous ink according to any one of claims 35 to 38, wherein The aqueous ink is an aqueous ink used to form printing or images on a substrate.
43. Aqueous ink as claimed in claim 42, wherein, The substrate is a non-liquid absorbing film.
44. The aqueous ink according to any one of claims 35 to 38, wherein The water-based ink is a water-based ink used for printing fiber products.
45. Aqueous ink as claimed in claim 44, wherein, The fiber product is cloth.
46. The aqueous ink according to any one of claims 35 to 38, wherein The water-based ink is water-based ink for inkjet printing, ink for flexographic printing, ink for offset printing, ink for digital stencil printing, ink for gravure printing or ink for screen printing.
47. A method for producing a resin emulsion for water-based ink, wherein the recording medium used in the water-based ink is a non-liquid-absorbing film, characterized in that: A monomer component containing a nitrogen atom-containing monomer is subjected to emulsion polymerization to prepare a resin emulsion containing emulsion particles, and the resin emulsion is mixed with a carboxylic acid polymer non-metallic salt, wherein the content of the nitrogen atom-containing monomer in the monomer component is 0.5 mass % to 10 mass %, At this time, a carboxylic acid polymer non-metal salt having a weight average molecular weight of 500 to 50,000 is used as the carboxylic acid polymer non-metal salt, the mass ratio of the nitrogen atom-containing monomer to the carboxylic acid polymer non-metal salt, i.e., the nitrogen atom-containing monomer / carboxylic acid polymer non-metal salt is adjusted to 10 / 90 to 90 / 10, a piperidine monomer is used as the nitrogen atom-containing monomer, and the amount of the carboxylic acid polymer non-metal salt is 0.3 to 10 parts by mass per 100 parts by mass of the non-volatile component of the resin emulsion, and the non-liquid-absorbing film is coated paper, polyester film, polyvinyl chloride film, polypropylene film, polyethylene film or nylon film.
Citation Information
Patent Citations
Manufacture of semiconductor device
JP1987058662A
Environmental protection type long-acting anti-mildew coating material preparation method
CN103468096A
Aqueous resin composition and method for producing the same
JP2015034295A
Aqueous ink composition
JP2015057455A
Resin composition
JP2018059007A